2015
DOI: 10.1080/01621459.2014.991394
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Longitudinal Multivariate Outcome Data From Couples Cohort Studies: Application to HPV Transmission Dynamics

Abstract: We consider a specific situation of correlated data where multiple outcomes are repeatedly measured on each member of a couple. Such multivariate longitudinal data from couples may exhibit multi-faceted correlations which can be further complicated if there are polygamous partnerships. An example is data from cohort studies on human papillomavirus (HPV) transmission dynamics in heterosexual couples. HPV is a common sexually transmitted disease with 14 known oncogenic types causing anogenital cancers. The binar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Transmission from man to woman or woman to man has been evaluated in six of the recent studies shown in Table 1. Three of the studies have detected that transmission of α-HPV occurs more likely from man to woman [4, 19, 20] and two from woman to man [16, 17]. The only study detecting β- and γ-HPV infection within a 6-week follow-up, so far, has not found any difference in transmission between sexes [6].…”
Section: Hpv Transmission In Heterosexual Couplesmentioning
confidence: 99%
“…Transmission from man to woman or woman to man has been evaluated in six of the recent studies shown in Table 1. Three of the studies have detected that transmission of α-HPV occurs more likely from man to woman [4, 19, 20] and two from woman to man [16, 17]. The only study detecting β- and γ-HPV infection within a 6-week follow-up, so far, has not found any difference in transmission between sexes [6].…”
Section: Hpv Transmission In Heterosexual Couplesmentioning
confidence: 99%
“…In this way, CL is free of the computational burden of inverting high-dimensional correlation matrices and benefits from an objective function that facilitates model selection. Pairwise CL has been used with longitudinal (Kuk and Nott (2000), Kong et al (2015)), spatial (Heagerty and and (1998), Arbia (2014)), spatiotemporal (Bai et al (2012), Bevilacqua et al (2012)), and genetic (Larribe and Fearnhead (2011)) data.…”
Section: Introductionmentioning
confidence: 99%
“…This fitting method alternates between optimal estimating equations for estimation of regression coefficients and pairwise likelihood (Varin et al, 2011) for estimation of dependence parameters. Recent applications of hybrid pairwise likelihood include pairwise comparison models (Cattelan and Varin, 2013) and multivariate longitudinal data (Kong et al, 2015). Pairwise likelihood estimation for the analysis of binary spatial data is discussed, for example, in Heagerty and Lele (1998), Varin et al (2005), Apanasovich et al (2008), Bai et al (2014) and .…”
Section: Introductionmentioning
confidence: 99%